FORM OF STANDARDIZATION AND STEREOTYPING PRACTICES THROUGH MESSAGE OF VIDEO ADS BUAVITA - Narendra, Asnurul Novia; Habsari, Sri Kusuma; Ardianto, Deny Tri (Seni Media Rekam ISI Surakarta, 2019)
This research focuses on the symbols contained in the four Buavita video ads, namely Buavita Mix Berries, Buavita Kelapa, Buavita Mangga, and Buavita Jambu. These ad videos seem to be able to segment the community into a type of society. The research aims to prove the existence of certain symbols in the Buavita advertisement video as a practice of hegemony and perpetuating gender inequality. This research uses descriptive qualitative method with four theories of cultural studies as the theoretical basis. The results showed that Buavita's ad-style healthy lifestyle became a trick of capitalism in inviting people to consume symbols and make profits. The video presentation of Buavita's advertisement is also a medium for the perpetuation of the concept of the traditional gender role that positions women as domestic agents, passive and consumptive, while men as non-domestic, active, and productive agents.